Kemampuan Pemecahan Masalah Kontekstual Materi Statistika Ditinjau dari Adversity Quotient - Hidayah, Ninik Nihayatul; Setyaningsih, Rini (Universitas Negeri Surabaya, 2024)
Problem solving competence is the ability of a person to carry out the problem solving process. This is he one of the skills a student must master after learning mathematics. Different students have different solutions when solving problems in statistical context. This is because each student has a different level of intelligence to solve problems. This intelligence is called Adversity Quotient (AQ). There are three AQ levels for him: Climber, Camper and Climber. The purpose of this study is to illustrate the ability of AQ to solve contextual problems of statistical material. This study was a descriptive study with a qualitative approach and was conducted in her 8th grade consisting of 3 of her students with different AQ levels. The research equipment used consisted of ARP, TPMS, and an interview guide. The results of this study suggested that, at the level of problem understanding, subjects who abandoned the problem were able to retell in their own language, which was different from that of the subjects who abandoned the problem, giving the language of the question a different meaning. During the planning stage, professional mountaineers understand the relationship between problems and statistical concepts and daily life and develop a very coherent and clear plan, whereas professional mountaineers and promoters develop a plan with a good understanding of the relationship between statistical concepts and daily life. During the execution phase of planning, professional movers and campers can find the right answers, but professional movers can also find the wrong answers. In the hindsight stage, the climber double-checks to reach the correct conclusion, but the climber and the climber can make fairly accurate conclusions without double-checking. Therefore, it is important for students and teachers to know problem-solving skills in the context of statistical material in order to improve comprehension and information comprehension in making logical conclusions using statistical ideas derived from statistical information about everyday problems.